Analisis Pengukuran Produktivitas Produksi Teh Hitam dengan Metode Objective Matrix - Robino Indan; Ridhonal Alviando (Universitas Putra Indonesia YPTK Padang, 2020)
PT. XYZ is a state-owned company engaged in the plantation sector and one of its branches is located in Kerinci,Jambi with its main product being Orthodox Black Tea. Inefficient and effective use of raw material, labor, energy and machinery during production activities encourages companies to increase productivity. Therefore, companies need to measure productivity to find out the dominant factors that affect productivity. The method used in productivity measurement is the Objective Matrix (OMAX) Method, so that the steps in this study referto the needs of matrix formation, namely: data collection, determination productivity criteria, calculation of ratios, determination of initial value, determination of the lowest ratio, determination of target values, and determination of weight.